Increasing growth of sorghum using vermicompost and dolomite planted in tidal soil - Febriza, Nur Indah (Journal of Smart Agriculture and Environmental Technology, 2023)
Sorghum is a cereal food that can grow on marginal land and is suitable for planting in dry or warm areas. The purpose of this study is to investigate the influence of vermicompost, dolomite, and a combination of vermicompost and dolomite on soil NPK levels, NPK uptake, growth, and production of sorghum plants (Sorghum bicolor L. Moench) on tidal soil. The research was conducted at the Greenhouse, and soil and plant NPK analysis was performed in the Soil Chemistry Laboratory, Biology and Soil Fertility Department, Faculty of Agriculture, Sriwijaya University. This research used a completely randomized factorial design with 2 factors, where the first factor consisted of 3 dosage levels of vermicompost: 0 ton/ha (V0), 2.5 ton/ha (V1), 5 ton/ha (V2), and 7.5 ton/ha (V3), and the second factor comprised 2 dosage levels of dolomite: 0 ton/ha (K1) and 0.404 ton/ha (K2). The results showed that vermicompost, dolomite, and the combination of vermicompost and dolomite had no significant effect on soil N, P, K levels, as well as N, P, K uptake, wet weight, dry weight, height, number of leaves, and sorghum panicle weight.